PENGARUH KONSENTRASI KITOSAN PADA EDIBLE COATING TERHADAP MASA SIMPAN BUAH PIR (Pyrus bretschneideri Rehd.) TEROLAH MINIMAL - Susilawati; Likia Salsa Billa; Zulferiyenni Zulferiyenni; Dewi Sartika (Jurusan Teknologi Hasil Pertanian, 2026)
After being cut, pears tend to undergo quality degradation and damage such as enzymatic browning, moisture loss, and textural changes. The use of chitosan concentration in edible coating solutions is an innovation that can be applied to minimally processed (fresh-cut) pears to inhibit the rate of such degradation. This study aims to determine the effect of chitosan concentration in edible coatings on the shelf life of minimally processed pears (Pyrus bretschneideri Rehd.) and to identify the optimal chitosan concentration capable of extending their shelf life according to the star method. The research was structured using a non-factorial Completely Randomized Design (CRD) based on different chitosan concentrations. The study consisted of six treatment levels: CK as the control, C1 (polyvinyl alcohol + 0.5% chitosan), C2 (polyvinyl alcohol + 1% chitosan), C3 (polyvinyl alcohol + 1.5% chitosan), C4 (polyvinyl alcohol + 2% chitosan), and C5 (polyvinyl alcohol + 2.5% chitosan), with four replications each. The results showed that the concentration of chitosan in the edible coating solution significantly affected the parameters of moisture content, weight loss, firmness, total soluble solids (TSS), and color. Based on the star method, the chitosan concentration that best maintained the freshness of the pears was treatment C4 (2% chitosan), with the following characteristics: moisture content of 84.60%, weight loss of 1.68%, firmness of 874.60 gf, total soluble solids of 14.35°Brix, and a lightness (L*) value of 70.03. Additionally, the Vitamin C content test for the best treatment (C4) yielded 0.634 mg/g on day 8 of storage.